Flow Pattern Transition of Fine Cohesive Powders in a Gas-Solid Fluidized Bed under Mechanical Vibrating Conditions. (2015) - Mawatari, Yoshihide; Hamada, Yasumasa; Yamamura, Masato; Kage, Hiroyuki
Abstract: In this study, the fluidization characteristics for fine cohesive powders under mechanical vibrating conditions were experimentally investigated. In a case of handling of fine cohesive powders with fluidized bed, stable gas channels and cracks were easily formed in the bed due to the strong cohesiveness acting among particles. A mechanical vibration is one of the methods to improve the fluidity of fine cohesive powders. In this study, we focused on the transition of the dominant bed flow pattern induced by mechanical bed vibrating conditions. The powders used in this study were different sizes (0.7 – 20 μm) and materials (silica, alumina, polymer). All powders belonged to group-C in the Geldart classification. The bed expansion ratio was lower in the relatively smaller vibration strengths regardless of the gas velocity, however, it steeply increased with larger a certain vibration strength. Form the visual observation of the bed, the bubble formation appeared with larger than such a critical vibration strength. This implied that the dominant bed fluidization pattern was transitioned from channeling behavior (group-C) to bubbling behavior (group-A or –AC) by the addition of the mechanical vibration.